SELECTIVE ARTERIAL EMBOLISATION IN TREATMENT HIGH-FLOW PRIAPISM: A CASE REPORT (Vietnam Journal of Community Medicine, 2022)
Introduction: Priapism is a rare condition, in which high-flow priapism is the least common(
Keywords: Priapism, high-flow priapism, non-ischaemic priapism, low-flow priapism, ischaemic priapism.